A Black Reading of “The Parable of the Talents” - Senokoane, B. B. (Tumi) (Black theology, 2020)
The explanation of Biblical texts has often been left unquestionable by both believers and unbelievers. This has led to absorbing problematic explanations. This culture of not questioning has become a problem of making the Bible a tool of miseducation, suppression and exploitation. Above everything, Black believers tend to read, translate and interpret the Bible through “White/masters eyes.” This article aims to conscientize Blacks or the working class to read the Bible from their perspective and experiences. In this context, Blacks are to be understood as the working class who should problematize “The Parable of the Talents.” The article will argue that “The Parable of the Talents” has been read wrongly and will propose a new way of reading this parable.